Photosynthesis in a different light: spectro-microscopy for in vivo characterization of chloroplasts - Peter, Sébastien; Zell, Martina B.; Blum, Christian; Stuhl, Alexander; Elgass, Kirstin; Sackrow, Marcus; Subramaniam, Vinod; Meixner, Alfred J.; Harter, Klaus; Maurino, Veronica G.; Schleifenbaum, Frank E. (Frontiers in Plant Science, 2014)
During photosynthesis, energy conversion at the two photosystems is controlled by highly complex and dynamic adaptation processes triggered by external factors such as light quality, intensity, and duration, or internal cues such as carbon availability. These dynamics have remained largely concealed so far, because current analytical techniques are based on the investigation of isolated chloroplasts lacking full adaptation ability and are performed at non-physiologically low temperatures. Here, we use non-invasive in planta spectro-microscopic approaches to investigate living chloroplasts in their native environment at ambient temperatures. This is a valuable approach to study the complex function of these systems, because an intrinsic property—the fluorescence emission—is exploited and no additional external perturbations are introduced. Our analysis demonstrates a dynamic adjustment of not only the photosystemI/photosystemII (PSI/PSII) intensity ratio in the chloroplasts but also of the capacity of the LHCs for energy transfer in response to environmental and internal cues.